STAGING COMMUNAL MEMORY: ANALYZING INTERGENERATIONAL TRAUMA AND RECONCILIATION IN MAHESH DATTANI’S FINAL SOLUTIONS - B. Krishnaiah (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Mahesh Dattani's Final Solutions dramatizes the entrenched difficulties in Hindu-Muslim relations in India, contextualizing them within a continuum of historical traumas and disputed cultural memory. This study contends that Dattani’s dramatic techniques—choral staging, fragmented narrative, and intergenerational dialogues—simultaneously expose and subvert cycles of communal prejudice. Utilizing trauma theory (Cathy Caruth, Dominick LaCapra) and cultural memory studies (Aleida Assmann, Marianne Hirsch), this study analyzes how the play portrays the endurance of communal memory as a manifestation of intergenerational trauma, whilst fostering a place for tentative reconciliation. The study demonstrates through meticulous analysis that Final Solutions transcends a mere dramatic portrayal of riots; it serves as an intervention in the politics of memory, seeking to redefine the ethical dimensions of inter-community interaction.